2016
DOI: 10.1186/s13098-016-0129-5
|View full text |Cite
|
Sign up to set email alerts
|

Neck circumference as a risk factor of screen-detected diabetes mellitus: community-based study

Abstract: BackgroundWhereas an increase of neck circumference (NC) had been recently identified as a new independent cardiovascular disease (CVD) and metabolic syndrome risk factor, similar assessments concerning screen-detected diabetes mellitus (SDDM) have not been made. Thyroid gland volume (ThV) can potentially affect NC however the significance of this influence concerning the risk of NC-related disease is unknown.MethodsWe performed a ThV-adjusted evaluation of NC within a population-based investigation of SDDM an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 23 publications
1
18
0
Order By: Relevance
“…Among 4 studies which assessed SE and SP of NC for prediction of type 2 diabetes [ 11 14 ], the maximum values of SE and SP was 80 and 67 in children [ 12 ], and 100 and 72 in adults. In studies which assessed insulin resistance [ 12 , 15 , 16 ], two studies reported a SE of 100 in boys, and 50 to 95 in girls.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Among 4 studies which assessed SE and SP of NC for prediction of type 2 diabetes [ 11 14 ], the maximum values of SE and SP was 80 and 67 in children [ 12 ], and 100 and 72 in adults. In studies which assessed insulin resistance [ 12 , 15 , 16 ], two studies reported a SE of 100 in boys, and 50 to 95 in girls.…”
Section: Resultsmentioning
confidence: 99%
“…Among them, Yan et al found the strongest association between high NC and MetS in both elderly men and women, with ORs of 11.53 and 7.69, respectively [ 9 ]. The association between high NC and DM was reported in few studies [ 9 , 14 , 18 , 19 ] where in ORs or RRs varied between 1.26 (1.06–1.50) and 2.07 (1.06–4.03).…”
Section: Resultsmentioning
confidence: 99%
“…A larger NC has also been associated with a higher WC and values and levels of metabolic syndrome components, including SBP, DBP, dyslipidemia, and hyperglycemia [ 14 16 ]. Studies have demonstrated that NC is positively associated with the incidence of T2DM [ 24 , 25 ] and that a larger NC has been associated with increased insulin resistance and various cardiometabolic risk factors, such as decreasing HDL levels and increasing plasma triglyceride levels among healthy Chinese adults [ 26 ]. Notably, insulin resistance is the core etiology of metabolic syndromes and is one of the principal pathogeneses of T2DM.…”
Section: Discussionmentioning
confidence: 99%
“…NC correlates with the cross‐sectional area of the neck muscles in MRI, and its measurement has been proven to have high intra‐and interrater reliability . In previous studies, the association of NC with obesity, sleep apnea syndrome, diabetes, cognitive impairment and heart disease risk has been reported . Only one previous report has focused on the association of NC with swallowing function; the report indicated that the NC of older individuals who require long‐term care was associated with undernutrition …”
Section: Introductionmentioning
confidence: 99%